1984
DOI: 10.1021/jm00367a013
|View full text |Cite
|
Sign up to set email alerts
|

A cannabinoid derived prototypical analgesic

Abstract: The synthesis and analgesic testing of 3-[4-(1,1-dimethylheptyl)-2-hydroxyphenyl]cyclohexanol (1) are described. Prior (SAR) studies led us to conclude that the pyran ring of 9-nor-9 beta-hydroxyhexahydrocannabinol (HHC) was not necessary for the expression of biological activity in this series of cannabinoids. Analysis of models and the use of molecular mechanics calculations suggested that a simpler compound, such as 1, would possess the biological activity of HHC. Compound 1 was prepared in nine steps from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 0 publications
0
55
0
2
Order By: Relevance
“…Pfizer Inc. has also reported many analogs of 1 and has described their synthesis with pharmacological data. 19,22,31,32) Additionally, various cannabinoid analogs are synthesized one after another and their pharmacological activity studied for the development of new useful drugs for the treatment of a number of diseases. 23,24) This situation alerts us that these described cannabinoid analogs other than 1 may be found as designer drugs or adulterants in illegal products in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pfizer Inc. has also reported many analogs of 1 and has described their synthesis with pharmacological data. 19,22,31,32) Additionally, various cannabinoid analogs are synthesized one after another and their pharmacological activity studied for the development of new useful drugs for the treatment of a number of diseases. 23,24) This situation alerts us that these described cannabinoid analogs other than 1 may be found as designer drugs or adulterants in illegal products in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…17,18) In the 1980s, a group at Pfizer Inc. explored the development of analgesics using potent synthetic cannabinoids. [19][20][21][22] After the discovery of cannabinoid receptors, type 1 (CB 1, central type) and type 2 (CB 2 , peripheral type), as well as the discovery of an endogenous cannabinoid, their physiological roles were elucidated; a number of cannabinoid analogs were then newly synthesized, and their pharmacological activity for the treatment of various diseases was studied. 23,24) Recently, cannabis abuse seems to have spread in Japan.…”
mentioning
confidence: 99%
“…In the past few decades, a number of analogs of Δ 9 -THC have been synthesized based on the partially reduced dibenzopyran structure of THC, and their structure-activity relationships were studied [12,13]. In the 1980s, a group at Pfi zer explored the development of analgesics using potent synthetic nontraditional cannabinoids, which lack the dibenzopyran structure present in the traditional cannabinoids but exhibit typical cannabinoid pharmacological effects [14][15][16][17][18][19][20][21][22]. On the other hand, D'Ambra et al [23] reported in 1992 that aminoalkylindoles, such as WIN-55212-2, were bound to a cannabinoid brain receptor with high affi nity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In the early 1980s a group at Pfizer explored the development of analgesics using the potent synthetic cannabinoid, (-)-9-nor-9β-hydroxyhexahydrocannabinol (HHC, 2), as a template. [5][6][7] This led to a series of nontraditional cannabinoids in which the oxygen containing pyran ring of THC was removed to provide a bicyclic system that retained the phenolic hydroxyl group of THC and the 9-hydroxyl of HHC. In common with the SAR developed for traditional cannabinoids it was found that potency was maximum with a 1,1-dimethylheptyl substituent at the 3-position of the aromatic ring and the 9-hydroxyl had the β-orientation.…”
Section: Introductionmentioning
confidence: 99%